Design Analysis Achievement Target Database Information System at SEAMEO RECFON - Dodi Suswandi; Ivan Hanfi; Widodo Widodo (International Journal Labs, 2023)
SEAMEO Regional Center for Food and Nutrition (RECFON), is an organization of Southeast Asian Ministers of Education in the field of food and nutrition. The activities carried out by SEAMEO RECFON already have a fairly good system, but there are several problems SEAMEO RECFON actively conducts education, research, training, and community empowerment activities so the need for up-to-date information on food and nutrition topics and services and facilities support all these activities is very important. This important task must be supported by adequate facilities, including the procurement of data processing and communication devices capable of supporting RECFON's activities. For this reason, the author takes the title